CSR as Corporate Political Activity: Observations on IKEA’s CSR Identity–Image Dynamics - Morsing, Mette (Journal of business ethics, 2015)
In this article, we develop a conceptual framework to understand how a company’s CSR identity becomes defined as a political activity destabilizing the strong identity–image relations. We draw on theories of political CSR and organizational identity–image relations to study how CSR emerges as a corporate political activity in a context where the corporate CSR work is first appreciated and later critiqued by the public in the wake of socio-political events. We analyse the micro-organizational processes in the context of macro-political level changes, and we refer to this as the ‘identity–image dynamics of political CSR’. Concretely, we describe in two vignettes how IKEA’s declared ‘apolitical and neutral’ CSR identity becomes entangled with national and international socio-political events that critically challenge the corporate engagement prior national understandings of citizenship rights. In this process, IKEA’s CSR identity becomes defined as a political and non-neutral activity. Our article contributes by bringing attention to the organizational level dynamics of political CSR by offering a conceptualization of how global and local socio-political events may disturb the alignment between CSR identity and image and challenge the corporate CSR work beyond managerial control.